Using Nonlinear Static Procedures for the Seismic Assessment of Irregular RC Buildings - Sousa, Romain (2020)
The application of Nonlinear Static Procedures (NSPs) to assess the seismic vulnerability of existing structures has become widely accepted and extensively used in the literature as well as in engineering practice. Nevertheless, their success in predicting the response of irregular buildings is not yet fully verified. The main goal of the present study is to evaluate the capability and accuracy of some of the existing nonlinear static procedures (N2 and ACSM, in this case) to estimate the seismic performance of irregular structures. In order to accomplish this objective, four existing buildings, irregular in plan and elevation, were subjected to an extensive number of nonlinear static and dynamic analyses. The comparisons, focused on both global and local response parameters provide first indications on the reliability of static procedures to estimate the actual response of irregular RC buildings.